Methods and associations of suicidality in Kenyan high school students : clinical and public health implications - Ndetei, David M. (Cambridge University Press, 2025)
Background: Most evidence on suicidal thoughts, plans and attempts comes from Western countries; prevalence rates may differ in other parts of the world.
Aims: This study determined the prevalence of suicidal thoughts, plans and attempts in high school students in three different regional settings in Kenya.
Method: This was a cross-sectional study of 2652 high school students. We asked structured questions to determine the prevalence of various types of suicidality, the methods planned or effected, and participants' gender, age and form (grade level). We provided descriptive statistics, testing significant differences by chi-squared and Fisher's exact tests, and used logistic regression to identify relationships among different variables and their associations with suicidality.
Results: The prevalence rates of suicidal thoughts, plans and attempts were 26.8, 14.9 and 15.7%, respectively. These rates are higher than those reported for Western countries. Some 6.7% of suicide attempts were not associated with plans. The most common method used in suicide attempts was drinking chemicals/poison (18.8%). Rates of suicidal thoughts and plans were higher for older students and students in urban rather than rural locations, and attempts were associated with female gender and higher grade level - especially the final year of high school, when exam performance affects future education and career prospects.
Conclusion: Suicidal thoughts, plans and attempts are prevalent in Kenyan high school students. There is a need for future studies to determine the different starting points to suicidal attempts, particularly for the significant number whose attempts are not preceded by thoughts and plans.